KAJIAN POTENSI KOMODITAS TANAMAN PANGAN DI KABUPATEN MINAHASA - Meilani A.E. Wowor; Esry O.H. Laoh; Theodora M. Katiandagho; Welson M. Wangke (COCOS, 2015)
ABSTRACTThis study aims to determine which areas that form the basis for certain food crops in Minahasa, and to know their growth and locational advantages in every district in Minahasa Regency from 2011 to 2012. The experiment was conducted using secondary data obtained from the Central Bureau of Statistics both at Minahasa and North Sulawesi Offices. Data were analyzed using Location Quotient (LQ) and Shift-Share analysis in the form of Proportional Shift and Differential Shift. The results showed that corn and sweet potato were the base commodities in most of the districts in Minahasa. Moreover, sweet potato had a rapid growth in nine districts, whereas corn had location advantages in eight districts.Keywords: crop, base commodity.